Investigation of CoCrFeNiMn high entropy alloy depositions during cold spray additive manufacturing - Akisin, Cletus John (2024)
Cold spray is steadily becoming a popular solid-state additive manufacturing (AM) and repair technique, referred to as cold spray additive manufacturing (CSAM). It is a material deposition technique that utilises the kinetic energy of microparticles to form dense deposits layer-by-layer on a target surface. Because of the solid-nature of the CSAM process, various components manufactured with CSAM have found applications in aero-engines as those components can withstand the extreme operating conditions of aero-engines. Since the CSAM process retains the initial microstructure of feedstock materials, being also an eco-friendly process, makes it a viable option for the deposition of several metals and alloys. Hence, substantially reducing environmental footprint and manufacturing cost.